New species and records of Antillocladius Sæther and Litocladius Mendes, Andersen et Sæther from Brazil and Costa Rica (Chironomidae: Orthocladiinae) - Mendes, Humberto F.; Andersen, Trond; Hagenlund, Linn K. (Zootaxa, 2011)
Antillocladius anandae sp. n., A. itatiaia sp. n. and Litocladius neusae sp. n. from Brazil, and L. chavarriai sp. n. from Costa Rica are described and illustrated as males. In addition, new records of A. antecalvus Sæther, A. arcuatus Sæther, A. brazuca Mendes et Andersen, A. folius Mendes, Andersen et Sæther, A. musci Mendes, Andersen et Sæther and Litocladius floripa Mendes et Andersen are given. Including the new species described below Antillocladius Sæther now comprises 27 species from the Neotropical, Nearctic and Oriental zoogeographical regions, while Litocladius Mendes, Andersen et Sæther comprises 5 species from the Neotropical region.